2019
DOI: 10.1097/md.0000000000015912
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged lumbosacral pain as the initial presentation in acute lymphoblastic leukemia in an adult

Abstract: Rationale: The differential diagnosis of conditions manifesting as bone and joint pain is complex. Although many individuals with acute leukemia experience bone pain, lumbosacral pain as an early feature of acute lymphoblastic leukemia (ALL) is rare. Patient concerns: Here we report a case of an adult who presented with a 7-month history of persistent lumbosacral pain which had become more severe during the previous month. Diagnoses: Prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
0
6
1
Order By: Relevance
“…More than 20% of children with ALL have bone pain at the onset, higher than that in adults with ALL. However, multiple bone destruction is rare in both children and adults with ALL ( 4 , 9 , 10 ). Among adult malignant tumors, multiple bone destruction incidence is 27%–35% in lung cancer, 25%–30% in breast cancer, 7%–30% in multiple myeloma, < 10% in malignant lymphoma, and < 1% in leukemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 20% of children with ALL have bone pain at the onset, higher than that in adults with ALL. However, multiple bone destruction is rare in both children and adults with ALL ( 4 , 9 , 10 ). Among adult malignant tumors, multiple bone destruction incidence is 27%–35% in lung cancer, 25%–30% in breast cancer, 7%–30% in multiple myeloma, < 10% in malignant lymphoma, and < 1% in leukemia ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were negative for CD2, CD3, CD5, CD7, CD8, CD11b, CD13, CD14, CD15, CD16, CD20, CD33, CD56, CD64, and CD117, consistent with the immunophenotype of B-cell ALL. The karyotype was 76 (3n), XX, -Y, +2, +4, +6, -7, +8, t (9:22) (q34.1:q11.2), +13, -15, +16, +17, +20, +21, +22 ( 4 )/46, XY ( 5 ). Leukemia fusion gene detection revealed BCR-ABL1 (P190) positivity.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Therefore, the patients can choose music by themselves, or the medical staff can designate certain types of music for the patients, so as to help the patients to relieve pain through the auxiliary effect of music. Some studies have found that in the process of using music for patients with advanced pain due to leukemia, music not only can reduce pain, but also can help patients to reduce anxiety and relieve depressive symptoms [17] . The analysis may be that music promotes the excitement of auditory pathway in the brain and inhibits the adjacent pain centers, thereby alleviating the pain in the patient.…”
Section: Musicial Pain Nursing Methodsmentioning
confidence: 99%
“…2 Clinical presentation of adults with ALL usually involves symptoms of lymphadenectasis, infections, anemia, pallor, bleeding, and bone pain. 3 Though vertebral compression fractures have been reported as initial signs of ALL in children [4][5][6] and middle-aged, [7][8][9] to the best of our knowledge, there have not been any previous reports of vertebral compression fractures as an initial manifestation of ALL in elderly people. Here, we reported on a case of elderly man in whom back pain associated with vertebral compression and collapse were presenting features of ALL.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Clinical presentation of adults with ALL usually involves symptoms of lymphadenectasis, infections, anemia, pallor, bleeding, and bone pain. 3 …”
Section: Introductionmentioning
confidence: 99%